2021
DOI: 10.1002/spy2.149
|View full text |Cite
|
Sign up to set email alerts
|

Digital forensic readiness in operational cloud leveraging ISO/IEC 27043 guidelines on security monitoring

Abstract: An increase in the use of cloud computing technologies by organizations has led to cybercriminals targeting cloud environments to orchestrate malicious attacks. Conversely, this has led to the need for proactive approaches through the use of digital forensic readiness (DFR). Existing studies have attempted to develop proactive prototypes using diverse agent‐based solutions that are capable of extracting a forensically sound potential digital evidence. As a way to address this limitation and further evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Various studies have been reported that investigate and recognize cybercrime [22,[31][32][33][34][35][36][37][38][39][40], data cracks [23,[41][42][43][44][45][46][47][48][49][50], and other digital risks [24,25,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: A Related Workmentioning
confidence: 99%
“…Various studies have been reported that investigate and recognize cybercrime [22,[31][32][33][34][35][36][37][38][39][40], data cracks [23,[41][42][43][44][45][46][47][48][49][50], and other digital risks [24,25,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: A Related Workmentioning
confidence: 99%
“…On the other hand, several models and frameworks have been proposed in the literature for drone and digital forensics to solve the challenges and issues of drone forensics [73][74][75][76][77][78][79][80][81][82].…”
Section: Machine Learning Techniques Used In the Drone Forensics Fieldmentioning
confidence: 99%
“…By definition, DFR has the capability of the system to efficiently gather the available relevant DE to be used in a court of law [43,47], hence minimizing investigation costs [48,49]. And DFR is the integrated management model to identify the cause of the incident and to have digital forensic evidence ready when needed for investigation [9,50].…”
Section: B Digital Forensic Readinessmentioning
confidence: 99%
“…The investigative processes class consists of in a forensic procedure. The concurrent processes class is the set of processes that run throughout all the 4 process classes in the digital investigation process [49,73].…”
Section: ) Digital Investigation Process Classesmentioning
confidence: 99%
See 1 more Smart Citation